1975
DOI: 10.1002/pen.760150410
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of aging effects of ABS polymers

Abstract: ABS (acrylonitrile‐butadiene‐styrene) plastics are one of the most common two‐phase commercial polymer systems. They consist of a continuous rigid phase (styrene‐acrylonitrile co‐polymer) in which the elastomer phase (polybutadiene grafted with styrene and acrylonitrile) is finely dispersed in the form of spherical particles. Because of their properties and relatively low cost compared to other engineering thermoplastics, ABS resins are now being used increasingly in fields of application involving severe agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…This has been simulated by repeated injection molding, two injection molding cycles have been carried out. Two injection molding cycles have been considered because in industrial applications the materials usually are not reprocessed more than twice due to its mechanical degradation as Casale et al (1975) and Eguiazabal and Nazabal (1990) suggested. The polymer was dried in an air oven before each processing cycle to minimize degradation reactions caused by moisture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been simulated by repeated injection molding, two injection molding cycles have been carried out. Two injection molding cycles have been considered because in industrial applications the materials usually are not reprocessed more than twice due to its mechanical degradation as Casale et al (1975) and Eguiazabal and Nazabal (1990) suggested. The polymer was dried in an air oven before each processing cycle to minimize degradation reactions caused by moisture.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Casale et al (1975) evaluated the effects of reprocessing conditions on mechanical properties by varying temperatures and dwell times. In this case material was ground and remolded five times.…”
Section: Introductionmentioning
confidence: 99%
“…(4) due to the exponential nature of t". The second factor is related to the degradation of ABS by molecular chain breaking, oxidation, and butadiene particle coelescence at the high temperatures used during FD extrusion (Casale et al, 1975;Kelleher, 1966). This temperature related degradation is being confirmed via comparison of the molecular weights and microstructures (i.e., the butadiene particle size distribution) of the bulk ABS with extruded FD-ABS.…”
Section: J/mol • K)mentioning
confidence: 99%
“…Therefore care must be taken during extruder compounding not to leave the ABS in the barrel for excessive periods of time otherwise the polymer could become discoloured [20]. In extreme cases where excessive degradation occurs, brittleness, 'pockets' of degraded polymer or even smoke and fume emission can occur.…”
Section: Compoundingmentioning
confidence: 99%
“…Grafted SAN on the surface of the polybutadiene particles forms a compatible link between the particles and the matrix. By varying the amount of the components, the manner by which they are combined and the size and number of elastomer particles, ABS resins can be manufactured to a wide specification range [20]. This range includes low to high impact, low gloss, glass reinforced, fire retarded, high heat and plating grades to name a few.…”
Section: Abs Polymermentioning
confidence: 99%